Analysis of Women's Participation in the Political and Social Processes of Afghanistan - YAR, Fayaz Gul Mazloum; ZAHID, Shamsurahman; MIAKHIL, Jan Mohammad (Indonesia Strategic Sustainability, 2024)
Purpose: This study examines the implementation of UN Security Council Resolution 1325 on women, peace, and security in Afghanistan, focusing on the Islamic Republic of Afghanistan's action plan.Methodology:The research employs a mixed-methods approach, combining quantitative and qualitative analysis, and is a field study. The sample consisted of 100 well-known activists in women's participation studies and advocacy, chosen based on their professional experience and interactions over the past fifteen years. Data collection involved distributing 110 questionnaires with 35 closed-ended and three open-ended questions, resulting in 101 valid responses. The study utilized books, reports, surveys, and existing scientific studies to categorize and present the findings.Findings: The study revealed that since adopting the National Action Plan for Women, Peace, and Security to implement Resolution 1325, the Afghan government and national and international partners have undertaken various initiatives to enhance women's social and political participation.Implication:Numerous challenges and obstacles remain, necessitating severe attention from the government, legislative bodies, and their.